1994
DOI: 10.1111/j.1432-1033.1994.tb19915.x
|View full text |Cite
|
Sign up to set email alerts
|

Undecagold cluster modified tRNAPhe from Escherichia coli and its activity in the protein elongation cycle

Abstract: An undecagold cluster (Au,,) of molecular mass 6200Da was attached to the 3-(3-amino-3-carboxypropy1)uridine at position 47 of tRNAPhe from Escherichia coli. This modified tRNA can be enzymically aminoacylated with phenylalanine in the reaction catalyzed by phenylalanyl-tRNA synthetase. Au,,-labeled Phe-tRNAPh' forms a ternary complex with the elongation factor Tu . GTP and is active in poly(U)-dependent poly(phe) synthesis. The Au,, modification does not hinder the specific binding of tRNA to distinct ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The labeling reaction was as described (Plumbridge et al, 1980;Blechschmidt et al, 1994;Fei et al, 2008) with minor modifications, and typically was carried out in a 100-ml volume by incubating up to 18 nM (4.54 mg/ml) of tRNA Phe with 0.52 mM (4 mg/ml) of Cy3 NHS ester in 0.1 M sodium bicarbonate buffer, pH 8.3, at room temperature for 5 h, followed by an overnight incubation at 48C. The reaction was stopped by addition of 1/10 volume of 3 M NaOAc, pH 5.5.…”
Section: Labeling Of Trna Phementioning
confidence: 99%
See 1 more Smart Citation
“…The labeling reaction was as described (Plumbridge et al, 1980;Blechschmidt et al, 1994;Fei et al, 2008) with minor modifications, and typically was carried out in a 100-ml volume by incubating up to 18 nM (4.54 mg/ml) of tRNA Phe with 0.52 mM (4 mg/ml) of Cy3 NHS ester in 0.1 M sodium bicarbonate buffer, pH 8.3, at room temperature for 5 h, followed by an overnight incubation at 48C. The reaction was stopped by addition of 1/10 volume of 3 M NaOAc, pH 5.5.…”
Section: Labeling Of Trna Phementioning
confidence: 99%
“…Current methods for chemical modification of tRNA molecules with fluorescent dyes are based on presence in certain tRNAs at their elbow positions of high reactive unusual nucleotides, such as 4-thiouridine (s 4 U) at position 8 or 3-(3-amino-3-carboxypropyl)uridine (acp 3 U) at position 47. Such nucleotides can be modified with maleimide or NHS-linked fluorophores (Plumbridge et al, 1980;Janiak et al, 1990;Blechschmidt et al, 1994;Blanchard et al, 2004). After the labeling reaction is completed, excess dye can be removed by phenol extraction and ethanol precipitation, or by using gel filtration, or by a dialysis step (Walker and Fredrick, 2008), followed by separation of labeled from unlabeled tRNA using RP HPLC.…”
Section: Fluorescence Labeling Of Trnamentioning
confidence: 99%
“…Alternatively, monofunctionalized Au 11 clusters were obtained by stoichiometric ligand place-exchange with suitably functionalized phosphine ligands [72] and subsequent chromatography. [77] These facilitated synthetic approaches allowed reliable labeling of a multitude of biomolecules for TEM detection such as proteins, [13,78] antibodies [79] and RNA, [80][81][82] whereby, in the latter case, it was shown that the undecagold label did not interfere with the translation process in the ribosome due to its minuscule size [83,84] -in contrast to its Au 55 counterpart. [85] Recently, N-heterocyclic carbine-monofunctionalized undecagold was reported to have unprecedented thermal stability and catalytic activity in the electroreduction of CO 2 .…”
Section: Pre-polymerized Ligandsmentioning
confidence: 99%
“…The labeled tRNA(Phe) no longer bound to the elongation factor (EF) Tu.GTP complex of Thermus thermophilus , which prevented is use as a probe to localize its binding sites. However, Blechschmidt et al (1993, 1994) reported an alternative approach: they used Phe-tRNA(Phe) containing 3-(3-amino-3-carboxypropyl) uridine at position 47, converted to a thiol derivative using 2-iminothiolane (Traut’s reagent). This was labeled with maleimido undecagold.…”
Section: Preparation and Microscopic Applications Of Gold Cluster mentioning
confidence: 99%